Gamma irradiation-induced effects on the electrical properties of HfO2-based MOS devices. Issue 1 (1st February 2016) - Manikanthababu, N.; Arun, N.; Dhanunjaya, M.; Nageswara Rao, S.V.S.; Pathak, A. P.
ABSTRACT: Hafnium Oxide (HfO2 ) thin films were synthesized by e-beam evaporation and Radio frequency magnetron sputtering techniques. Au/HfO2 /Si-structured Metal Oxide Semiconductor capacitors have been fabricated to study the effects of gamma irradiation on the electrical properties, leakage current versus voltage (I–V) and capacitance versus voltage (C–V) characteristics, as a function of irradiation dose. Systematic increase in leakage current as well as accumulation capacitance has been observed with increase in the irradiation dose. The influence of gamma irradiation and pre-existing defects on the evolution of oxide and interface traps have been studied in detail.